Pengaruh Teknik Afirmasi untuk Meningkatkan Self-Efficacy pada Mahasiswa Akhir Saat Menghadapi Skripsi - Tobing, Elalita Rumondang; Agustina, Menik Tetha (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effect of affirmation techniques on enhancing self-efficacy among final-year students facing thesis writing. Students often experience pressure and anxiety that can hinder their academic performance, especially when preparing their theses. Self-efficacy, defined as an individual's belief in their ability to achieve specific outcomes, plays a crucial role in overcoming these challenges. This research employs a quantitative experimental method involving 10 final-year students in Semarang City. Data were collected using the Generalized Self-Efficacy Scale and analyzed using the Paired Sample t Test. The results indicate a significant increase in students' self-efficacy levels after the application of affirmation techniques, with a pre-test mean score of 16.60 and a post-test mean score of 31.80. These findings suggest that positive affirmations can serve as an effective tool for enhancing students' motivation and confidence in completing their theses. The study recommends the integration of positive affirmation programs in academic guidance at higher education institutions to support students in facing academic challenges.